Comprehensive study of the dynamic interaction between SO2 and acetaldehyde during alcoholic fermentation. (October 2020) - Ochando, Thomas; Mouret, Jean-Roch; Humbert-Goffard, Anne; Aguera, Evelyne; Sablayrolles, Jean-Marie; Farines, Vincent
Graphical abstract: Highlights: Yeast growth starts only when free SO2 reaches approximately 5 mg L −1 . Sulphites induce major disruptions in the NADPH/NADP + redox equilibrium. Sulphites impact synthesis of aromas related to both sulfur and carbon metabolism. Abstract: In this work, we focused on the effect of the initial content of SO2 in synthetic grape juice on yeast metabolism linked to the production of acetaldehyde. Lengthening of the lag phase duration was observed with an increase in the initial SO2 content. Nevertheless, an interesting finding was a threshold value of an initial SO2 content of 30 mg L −1 in the juice led to equilibrium between intracellular SO2 diffusion and SO2 production from the sulfate pool by yeast. The ratios of free and bound acetaldehydes were measured during fermentation, and the maximum accumulation of free acetaldehyde was observed when SO2 concentration equilibrium between diffusion and production was reached in the fermenting juice. Moreover, it was observed that SO2 addition resulted in significant changes in the synthesis of aroma compounds. Production of volatile molecules related to sulfur metabolism (methionol) was changed. But, more surprisingly, synthesis of some volatile carbon compounds (diacetyl, isoamyl alcohol, isobutyl alcohol, phenyl ethanol and their corresponding esters) was also altered because of major disruptions in the NADPH/NADP + redox equilibrium. Finally, we demonstrated that acetaldehyde bound to SO2 could not be metabolized by the yeast during the time course of fermentation and that only free acetaldehyde could impact metabolism.